AMPA receptor antagonist CFM-2 decreases survivin expression in cancer cells - Ruiz, Domingo; Staufner, Christian (Anti-cancer agents in medicinal chemistry, 2018)
Background: Glutamate receptors are widely expressed in different types of cancer cells. α-Amino-3- - hydroxy-5-methyl-4-isoxazolepropionate (AMPA) ...
Gesehen am 16.05.2019